Optimalisasi Digital Public Relations melalui Dialogic Communication pada Situs Web Pemerintah Kabupaten Mojokerto - Tiffany Nur Alifiya Sulaiman; Rachmat Kriyantono; Zulkarnain Nasution (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study is a quantitative descriptive study that aims to analyze the effectiveness of the Mojokerto Regency Government website as a two-way communication media in the context of Digital Public Relations. Using the Dialogic Communication Theory approach (Kent & Taylor, 1998), this study assesses five main indicators, namely dialogic loop, usefulness of information, generation of return visits, intuitiveness/ease of interface, and rule of conservation visits. Ordinal data were obtained through documentation of uploads on the mojokertokab.go.id site and analyzed using univariate techniques based on frequency distribution. The results showed that the website had varying performance. The indicators of usefulness of information and ease of interface obtained an optimal score of 100%, indicating that the site provides relevant information and is easily accessible to users. However, the indicators of dialogic loop and generation of return visits only reached 20%, indicating a lack of interactivity and a low rate of repeat visits. Overall, with an average effectiveness of 60%, the website is categorized as